Social-political and vaccine related determinants of COVID-19 vaccine hesitancy in Tanzania: A qualitative inquiry. - Sally Mtenga; Grace Mhalu; Brianna Osetinsky; Kaushik Ramaiya; Tani Kassim; Brady Hooley; Fabrizio Tediosi (PLOS Global Public Health, 2023)
Vaccines have played a critical role in the response to the COVID-19 pandemic globally, and Tanzania has made significant efforts to make them available to the public in addition to sensitizing them on its benefit. However, vaccine hesitancy remains a concern. It may prevent optimal uptake of this promising tool in many communities. This study aims to explore opinions and perceptions on vaccine hesitancy to better understand local attitudes towards vaccine hesitancy in both rural and urban Tanzania. The study employed cross-sectional semi-structured interviews with 42 participants. The data were collected in October 2021. Men and women aged between 18 and 70 years were purposefully sampled from Dar es Salaam and Tabora regions. Thematic content analysis was used to categorize data inductively and deductively. We found that COVID-19 vaccine hesitancy exists and is shaped by multiple socio-political and vaccine related factors. Vaccine related factors included worries over vaccine safety (e.g., death, infertility, and zombie), limited knowledge about the vaccines and fear of the vaccine's impact on pre-existing conditions. Participants also found it paradoxical that mask and hygiene mandates are expected even after vaccination, which further exacerbated their doubts about vaccine efficacy and their hesitancy. Participants possessed a range of questions regarding COVID-19 vaccines that they wanted answered by the government. Social factors included preference for traditional and home remedies and influence from others. Political factors included inconsistent messages on COVID-19 from the community and political leaders; and doubts about the existence of COVID-19 and the vaccine. Our findings suggest that the COVID-19 vaccine is beyond a medical intervention, it carries with it a variety of expectations and myths that need to be addressed in order to build trust and acceptance within communities. Health promotion messages need to respond to heterogeneous questions, misinformation, doubts, and concerns over safety issues. An understanding of country-specific perspectives toward COVID-19 vaccines can greatly inform the development of localized strategies for meaningful uptake in Tanzania.